Opium: An emerging risk factor for gastric adenocarcinoma. Issue 2 (13th February 2013) - Shakeri, Ramin; Malekzadeh, Reza; Etemadi, Arash; Nasrollahzadeh, Dariush; Aghcheli, Karim; Sotoudeh, Masoud; Islami, Farhad; Pourshams, Akram; Pawlita, Michael; Boffetta, Paolo; Dawsey, Sanford M.; Abnet, Christian C.; et al.
<x xml:space="preserve">Abstract</x> Opium use has been associated with higher risk of cancers of the esophagus, bladder, larynx, and lung; however, no previous study has examined its association with gastric cancer. There is also little information on the associations between hookah (water pipe) smoking or the chewing of tobacco products and the risk of gastric cancer. In a case‐control study in Golestan Province of Iran, we enrolled 309 cases of gastric adenocarcinoma (118 noncardia, 161 cardia and 30 mixed‐location adenocarcinomas) and 613 matched controls. Detailed information on long‐term use of opium, tobacco products and other covariates were collected using structured and validated lifestyle and food frequency questionnaires. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were obtained using conditional logistic regression models. Opium use was associated with an increased risk of gastric adenocarcinoma, with an adjusted OR (95% CI) of 3.1 (1.9–5.1), and this increased risk was apparent for both anatomic subsites (cardia and noncardia). There was a dose‐response effect, and individuals with the highest cumulative opium use had the strongest association (OR: 4.5; 95% CI: 2.3–8.5). We did not find a statistically significant association between the use of any of the tobacco products and risk of gastric adenocarcinoma, overall or by anatomic subsite. We showed, for the first time, an association between opium use and gastric adenocarcinoma. Given that opium use is a traditional practice in many parts of the world, these results are of public health significance.